Heerfordt’s Syndrome Presenting with Recurrent Facial Nerve Palsy : Case report and 10-year literature review - Preetam Chappity; Rajeev Kumar; Anjan K. Sahoo (Sultan Qaboos University Medical Journal, 2015)
Heerfordt’s syndrome is defined as a combination of facial palsy, parotid swelling, uveitis and fever in sarcoidosis cases. Heerfordt’s syndrome as a cause of facial palsy is very rare. We report a case of alternating facial nerve palsy in a 52-year-old female initially treated for Bell’s palsy. The patient was referred to the All India Institute of Medical Sciences, Bhubaneswar, India, in January 2013 for clinical evaluation. She was found to have a parotid swelling and anterior intermediate uveitis. A pathoradiological evaluation suggested sarcoidosis and a final diagnosis of Heerfordt’s syndrome was made. Steroid treatment was initiated which led to an improvement in the facial palsy and uveitis as well as the disappearance of the parotid swelling with a corresponding decrease in angiotensin-converting enzyme levels. An English literature review was carried out to analyse the varied presentation of this syndrome. The analysis focused on presenting symptoms, biochemical markers and radiological findings of Heerfordt’s syndrome cases.